Analysis of the Validity of Physics E-Modules Using the Problem-Based Learning (PBL) Model in Magnetism Material to Facilitate the Improvement of Critical Thinking Skills in High School Students - Lubis, Putria Ersyah Karmita (PILLAR OF PHYSICS EDUCATION, 2025)
The purpose of this research is to design and evaluate the validity of a physics e-module based on the PBL model for the topic of magnetism, aimed at enhancing high school students’ critical thinking skills. The study adopts the Plomp development model, encompassing the Preliminary Research stage and the Development or Prototyping Phase. Three physics lecturers from the Faculty of Mathematics and Natural Sciences at Padang State University participated as expert validators. The evaluation instruments addressed seven components: content accuracy, instructional design, visual presentation, e-module features, alignment with PBL syntax, indicators of critical thinking skills, and software integration. Data analysis was carried out using the Aiken’s V coefficient. The needs assessment revealed that students’ critical thinking skills in magnetism remain underdeveloped due to predominantly teacher-centered instruction and limited use of interactive learning resources. The e-module developed incorporates magnetism content, student worksheets, practice questions aligned with critical thinking indicators, and interactive media such as images, videos, and PhET simulations, all presented with intuitive navigation. Validation yielded an average score of 0.96, placing it in the “highly valid” category across all criteria. These results suggest that the e-module is a viable alternative learning resource for physics instruction.